Value of life year and cost-effectiveness thresholds: The case of Poland - Olimpia Markiewicz (Central European Economic Journal (CEEJ), 2021)
Objective: The objective of this article is to examine how people value two different attributes of Value of Life Year (VOLY): life expectancy and the quality of life. The results of the first VOLY estimations conducted in Poland are discussed and compared with Polish cost-effectiveness thresholds for medical treatments in the period 2008-2020. Methodology: The Discrete Choice Experiment (DCE) method was used to value two attributes of VOLY: increase in life expectancy and improvement in the quality of life. Main findings: The VOLY research was conducted in two populations: general and dialysis. Depending on their current health status, people value increased life expectancy and improvement in health quality differently. In light of these results, the VOLY should be differentiated. Also in the Quality Adjusted Life Year (QALY) indicator, the weights of the attributes of length and quality of life should be varied according to different states of health. A uniform cost-effectiveness threshold is not justified from the perspective of stated preferences. Cost-effectiveness thresholds based on demand-side values should be differentiated. Current Polish cost-effectiveness thresholds are overestimated compared to valuations based on stated preferences. Contributions: The article presents the first estimations of two attributes of VOLY: life expectancy and the quality of life, carried out in Poland.
Keywords: Q51; I18; D12; 330; Cost-Effectiveness Threshold; Discrete Choice Experiment (DCE); Quality Adjusted Life Year (QALY); Value of Life Year (VOLY); Value of Statistical Life (VSL)